Application Of Graph Coloring Using Wilch-Powell In Scheduling Lectures At Dharmas University Indonesia - Dwi Novri Asmara; Anti Estika Hader; Muhammad Zikrul Hanan (Universitas Wiralodra, 2025)
Node coloring in graph theory can be used in course scheduling. The urgent problem in this research is the frequent scheduling conflicts between one lecturer and different courses simultaneously, especially at Faculty of Teacher training and Education, Dharmas Indonesia University. This research aims to determine the appropriate course scheduling to avoid conflicts between lecturers and various courses. In determining the course schedule, the researcher applies the Wilch-Powell algorithm. The method used is deductive axiomatic, derived from existing theorems, and then node coloring is applied to the graph representation of Faculty of Teacher training and Education, Dharmas University Indonesia's course scheduling. Based on the research, a teaching matrix for Faculty of Teacher training and Education, Dharmas University Indonesia lecturers for the even semester of the 2024/2025 academic year was obtained with five different colors. The five colors represent the scheduling of 19 courses for the mathematics program, 17 courses for the early childhood education program and English education program, each with five different colors without any conflicts, requiring four classrooms.